Are clinical parameters sufficient to model gait patterns in patients with cerebral palsy using a multilinear approach?. Issue 7 (18th May 2016) - Bonnefoy-Mazure, Alice; Sagawa, Yoshisama; Pomero, Vincent; Lascombes, Pierre; De Coulon, Geraldo; Armand, Stéphane
Abstract : The aim of this study was to evaluate whether clinical parameters are sufficient using, a multilinear regression model, to reproduce the sagittal plane joint angles (hip, knee, and ankle) in cerebral palsy gait. A total of 154 patients were included. The two legs were considered (308 observations). Thirty-six clinical parameters were used as regressors (range of motion, muscle strength, and spasticity of the lower). From the clinical gait analysis, the joint angles of the sagittal plane were selected. Results showed that clinical parameter does not provide sufficient information to recover joint angles and/or that the multilinear regression model is not an appropriate solution.